Small-scale deformation behaviour of the AlCoCrFeNi2.1 eutectic high entropy alloy. Issue 17 (2nd September 2022) - Singh, Shailesh Kumar; Kumar, Govind; Babu, Pokula Narendra; Pal, Snehanshu; Vashistha, Saurabh; Azam, M. S.; Dixit, Saurabh
ABSTRACT: Novel methods to probe and evaluate the mechanical properties of High entropy alloy are gaining popularity to accelerate the development of new material for structural application and for establishing the physics-based mechanical property models. Nanoindentation techniques are predominantly suitable for evaluating the properties of materials in which deformation volumes can be cautiously controlled, and indentation can be applied to probe the properties of specific phases or features present within the microstructure. The current investigation is based on the plastic deformation response of Eutectic High Entropy Alloy, AlCoCrFeNi2.1, using experimental and computational approaches. In this paper, the plastic deformation of eutectic high entropy alloy AlCoCrFeNi2.1 is investigated using nanoindentation over a broad range of strain rates at room temperature to probe the mechanical properties of Eutectic High Entropy Alloy, AlCoCrFeNi2.1 and also to understand its elasto-plastic behaviour of BCC and FCC phase present in the alloy. In order to capture the deformation mechanism of material under the tip of the nano-indenter as well as to predict the load variation with depth, molecular dynamic simulation is performed. A characteristic load-depth curve has also been generated from the developed model, which is in good agreement with the experimental one. These findings will lead to understanding the phase-specific contribution to bulk mechanical response of multicomponent alloys and aid in designing structural materials with high fracture toughness.